Inflation Threshold Levels and Economic Growth in the Franc Zone Countries - Sanga, Dimitri; Gui-Diby, Steve Loris (World Bank, Washington, DC, 2020)
This paper examines the growth-inflation nexus in Franc zone currency unions. It aims at estimating the inflation threshold above which additional inflationary pressures adversely affect economic expansion. It uses cointegration methods that are applied to data from 14 African countries from the Franc zone over 1970-2018. Based on country-level data, the results indicate that it is possible to increase the threshold levels used by regional central banks to 5.4-5.6 percent in the Central African Monetary Union and 4.3-4.5 percent in the West African Monetary Union. Homogeneous cointegration panel data analyses confirm the need to increase the threshold in Central African Monetary Union countries but do not in the West African Monetary Union countries.